Perceptions of Plagiarism by STEM Graduate Students: A Case Study. - Leonard, Michelle; Schwieder, David; Buhler, Amy; Bennett, Denise; Royster, Melody (Science & Engineering Ethics, 2015)
Issues of academic integrity, specifically knowledge of, perceptions and attitudes toward plagiarism, are well documented in post-secondary settings using case studies for specific courses, recording discourse with focus groups, analyzing cross-cultural education philosophies, and reviewing the current literature. In this paper, the authors examine the perceptions of graduate students in science, technology, engineering, and mathematics (STEM) disciplines at the University of Florida regarding misconduct and integrity issues. Results revealed students' perceptions of the definition and seriousness of potential academic misconduct, knowledge of institutional procedures, and views on faculty actions, all with a focus on divergences between US and internationally-educated students. The open-ended questions provide anecdotal evidence to highlight personal experiences, positive and negative, aimed at the faculty, international students and undergraduates. Combined, these findings outline an important part of the campus academic integrity culture at a major American university. Recommendations for local actions also are discussed.